Characterization of Blood Monocyte Phenotype in Patients With Endometrial Cancer. Issue 9 (1st November 2012) - Brooks, Nicole; Stojanovska, Lily; Grant, Peter; Apostolopoulos, Vasso; McDonald, Christine F.; Pouniotis, Dodie S.
Abstract : Background: Endometrial tumors induce various tumor escape mechanisms that result in immunosuppression in patients and, ultimately, tumor progression. Blood monocytes are able to exhibit potent cytotoxic action against tumor cells where novel immunotherapeutics targeting antigen-presenting cells including dendritic cells, and blood monocytes are being used as a means of delivering immunogens to stimulate an antitumor and, ultimately, therapeutic response. This study shows that peripheral blood monocytes from patients with endometrial cancer show functional deficiencies, and these deficiencies can be characterized by phenotypic changes as well as altered cytokine secretion. Methods: This study assessed the phenotypic changes of peripheral blood monocytes by flow cytometry as well as the functional status via cytokine production measured by enzyme-linked immunosorbent assay in patients with endometrial cancer versus controls. Results: Altered blood monocyte phenotype incorporating a decrease in costimulatory and adhesion factor expression and increased expression of vascular endothelial growth factor receptor 1 in patients with endometrial cancer versus controls. Increased interleukin 12 and decreased interleukin 10 secretion by blood monocytes in patients with endometrial cancer were also observed. Conclusions: These findings showed that peripheral blood monocytes from patients with endometrial cancer show an altered phenotype and cytokine secretion when compared with controls. Limitations to this study include the small sample size, the need to investigate the effect of phenotype and cytokine changes in functional assays, as well as future studies investigating the effect on tumor-associated macrophages from endometrial tissue from cancer versus control patients. Nevertheless, these findings suggest that peripheral blood monocyte induced immunosuppression in endometrial cancer and implications in the design of future immunotargeting therapies remain to be elucidated.